GIS-Based Investigation of Lightning Activity with Its Meteorological and Topographical Correlates on a 500 kV Transmission Line in Peninsular Malaysia - Nurzanariah Roslan; Ungku Anisa Ungku Amirulddin; Mohd Zainal Abidin Ab Kadir; Noradlina Abdullah (International Journal of Integrated Engineering, 2026)
Climate change has caused a sudden surge in meteorological hazards in recent years, such as lightning strikes that have been a considerable challenge to transmission lines, causing flashovers, equipment damage, and outages. This study proposes a new method utilized Geographic Information System (GIS) integrated with Principal Component Analysis (PCA) to investigate the correlation of lightning, meteorology, and topography on the 500 kV transmission line A-B in Peninsular Malaysia from 2015 to 2017. This study utilized data on lightning, weather, topography and transmission lines from various sources. PCA was used to perform the analysis of the relation between lightning activity, elevation, and meteorological variables including temperature, rainfall, wind speed, and pressure. The study results show that lightning Ground Flash Density (GFD) exhibits positive correlations with elevation (r= 0.16) and rainfall (r= 0.18) and negative correlation with temperature (r= -0.13), wind speed (r= -0.34) and pressure           (r= -0.49). PCA further reveals that lightning GFD is most strongly associated with elevation while showing not largely correlated with warm, windy and elevated pressure conditions along the selected transmission line. These findings suggest that lightning activity along transmission line A-B is more strongly influenced by elevation than other meteorological variables. Identifying the factors that govern lightning occurrences is crucial in characterizing lightning distribution across Malaysia’s complex terrain. Understanding these correlations helps researchers and engineers better identify high-risk zones, forecast lightning-prone areas, and integrate these insights into spatial planning and grid design. This approach can be applied to other transmission lines, potentially improving the reliability of power grids through effective protection systems.